The equalizer (Sony Pictures Home Entertainment, 2014)
McCall, a man who believes he has put his mysterious past behind him and dedicated himself to beginning a new, quiet life. But when McCall meets Teri, a young girl under the control of ultra-violent Russian gangsters, he can't stand idly by; he has to help her. Armed with hidden skills that allow him to serve vengeance against anyone who would brutalize the helpless, McCall comes out of his self-imposed retirement and finds his desire for justice reawakened.

Noah (2014)
A man is appointed by God to carry out a crucial mission of rescue before a calamitous flood destroys the world.

Thor, the dark world (Marvel cinematic universe, 8,, 2014)
Thor fights to restore order across the cosmos, but an ancient race led by the vengeful Malekith returns to plunge the universe back into darkness. Faced with an enemy that even Odin and Asgard cannot withstand, Thor must embark on his most perilous and personal journey yet, one that will reunite him with Jane Foster and force him to sacrifice everything to save us all.

Rogue One (Buena Vista Home Entertainment, 2017)
In a period of great conflict, a group of unlikely heroes led by Jyn Erso, a daring fugitive, and Cassian Andor, a rebel spy, band together on a desperate mission to steal the plans to the Death Star, the Empire's ultimate weapon of destruction.

Divergent (Summit Entertainment, LLC, Summit Entertainment, 2014)
In a future world where people are divided into five distinct factions based on human virtues, Tris Prior is warned she is Divergent and will never fit into any one group. When she discovers a conspiracy by a faction leader to destroy all Divergents, Tris must learn to trust in the mysterious Four and together they must find out what makes being Divergent so dangerous before it's too late.

Captain Phillips (Sony Pictures Home Entertainment, 2014)
Based on the true story of Captain Richard Phillips and the 2009 hijacking by Somali pirates of the US-flagged MV Maersk Alabama, which was the first American cargo ship to be hijacked in two hundred years.

Live Die Repeat: Edge of tomorrow (Warner Home Video, 2014)
In a near future, an alien race has hit the Earth in an unbeatable assault. Major William Cage has never seen a day of combat, but is dropped into a suicide mission and killed within minutes. Cage now finds himself thrown into a time loop-forcing him to live out the same day over and over, fighting and dying each time. With each "life", Cage learns more fighting skills, so that when he and warrior Rita Vrataski take the fight to the aliens, they are one step closer to defeating the enemy.

Jurassic Park collection : Jurassic Park (Universal, 2015)
A wealthy entrepreneur invites a top paleontologist, a paleobotanist, a mathematician/theorist, and his two eager grandchildren to visit his secret island theme park featuring living dinosaurs cloned from prehistoric DNA.
Jurassic Park, The Lost World: Jurassic Park, Jurassic Park III

Big hero 6 (Disney DVD, ,, 2015)
Baymax is a lovable personal companion robot, who forms a special bond with robotics prodigy Hiro Hamada. When a devastating turn of events catapults them into the midst of a dangerous plot unfolding in the streets of San Fransokyo, Hiro turns to Baymax and his diverse group of friends, adrenaline junkie Go Go Tomago, neatnik Wasabi, chemistry whiz Henry Lemon and fanboy Fred, who transform into a band of unlikely heroes.

The shape of water (Twentieth Century Fox Home Entertainment, Fox Home Entertainment, 2018)
In a secret government laboratory, a mute custodian befriends an amphibian human-like creature.

Snow White & the huntsman (Universal Studios Home Entertainment, 2012)
Snow White is the only person in the land fairer than the evil queen who is out to destroy her. But what the wicked ruler never imagined is that the young woman threatening her reign has been training in the art of war with a huntsman who was dispatched to kill her.

Maleficent (Disney DVD, ,, 2014)
A beautiful, pure-hearted young woman, Maleficent has an idyllic life growing up in a peaceable forest kingdom, until one day when an invading army threatens the harmony of the land. Bent on revenge, Maleficent faces a battle with the invading king's successor and, as a result, places a curse upon his newborn infant Aurora. As the child grows, Maleficent realizes that Aurora holds the key to peace in the kingdom, and perhaps to Maleficent's true happiness as well.

A dog's journey (Universal, 2019)
Beloved dog Bailey is given an instruction by his boy Ethan -- no longer a boy -- to protect Ethan's granddaughter CJ at any cost. Again, Bailey takes this command to heart, through several lives, always finding his way home no matter what.

The peanut butter falcon (Lionsgate, 2019)
An adventure story set in the world of a modern Mark Twain that begins when Zak, a young man with Down syndrome, runs away from a nursing home where he lives to chase his dream of becoming a professional wrestler and attending the wrestling school of the Salt Water Redneck. Through circumstances beyond their control, Tyler, a small-time outlaw on the run, becomes Zak's unlikely coach and ally.

Avengers: infinity war (2018)
As the Avengers and their allies have continued to protect the world from threats too large for any one hero to handle, a new danger has emerged from the cosmic shadows: Thanos. A despot of intergalactic infamy, his goal is to collect all six Infinity Stones, artifacts of unimaginable power, and use them to inflict his twisted will on all of reality.

The resistance fighter (Shout Factory, 2020)
It tells the incredible true story of the Polish 'James Bond,' the legendary courier from Warsaw, a spy whose lonely mission could decide the fate of Poland and World War II. Based on a true story, this action-thriller follows real-life Polish war hero Jan Nowak-Jezioranski, a man of extraordinary courage, who served as an emissary between the commanders of Poland's resistance movement and the Polish government in exile in London at the height of the Second World War.

Inferno (Sony Pictures Home Entertainment, 2017)
When Robert Langdon wakes up in an Italian hospital with amnesia, he teams up with Sienna Brooks, a doctor he hopes will help him recover his memories. Together, they race across Europe and against the clock to stop a madman from unleashing a global virus that would wipe out half of the world's population.

Toy story 4 (Disney, 2019)
Woody has always been confident about his place in the world and that his priority is taking care of his kid, whether that's Andy or Bonnie. But when Bonnie adds a reluctant new toy called 'Forky' to her room, a road trip adventure alongside old and new friends will show Woody how big the world can be for a toy.

Django unchained (Anchor Bay Entertainment, 2013)
Django, a former slave turned hired gun, heads back to the plantation to free his wife, Broomhilda, from the tyrannical plantation owner Calvin Candie, with the help of a German bounty hunter, Dr. King Shultz.

Ice age: Dawn of the dinosaurs (20th Century Fox Home Entertainment, 2009)
Scrat is still trying to nab the ever-elusive nut and maybe finding true love; Manny and Ellie await the birth of their mini-mammoth; Diego the saber-toothed tiger wonders if he's growing too 'soft' hanging with his pals; and Sid the sloth gets into trouble when he creates his own makeshift family by hijacking some dinosaur eggs. On a mission to rescue the hapless Sid, the gang ventures into a mysterious underground world, where they have some very close encounters with dinosaurs, battle flora and fauna, run amuck, and meet a relentless, one-eyed, dino-hunting weasel named Buck.